Awareness and Acceptability of Reversible Contraceptive Methods in Post-natal Females in a Tertiary Care Setting: A Cross-sectional Study - Bhargav Pandurang Sawant Dessai; Malavika Krishnan; Hemangini K. Shah; Lorraine Edith Costa Noronha (Journal of Medical Evidence)
Background: The usage of modern contraceptives has increased in the Indian population according to the National Health and Family Survey-5 and a large chunk of this included sterilisation. The females undergoing sterilisation are usually multiparous women with poor birth spacing and post-natal complications. Hence, it is important to increase the percentage of women using reversible methods of contraception which can be done by counselling them about these methods. Aim: To study the awareness and acceptability of reversible contraceptive methods. Materials and Methods: A cross-sectional study was conducted in the obstetric wards of the only government tertiary care hospital in Goa. Females aged above 18 years who had undergone delivery at the tertiary hospital and were admitted for post-natal care in post-natal wards constituted the study participants. The study questionnaire included sociodemographic and obstetric parameters. Individual, in-depth interviews were conducted on the 2nd day post-delivery about their views on modern contraception and amongst past contraceptive users type and reason to use the contraceptives were ascertained. Proportions of women opting for any one of the contraceptive methods pre- and post-counselling were recorded and compared. Results: Amongst the 18–36-year-old married women, the mean age of participants was 24.55 ± 2.62, 137 (38%) were using the modern contraceptive method. 55 (16%) used pills, 15 (4%) used intrauterine contraceptive device, whereas 67 (18%) used condoms as a contraceptive measure, whereas emergency contraception was used by 18 (5%). Amongst the 223 (62%) of the participants who were not using modern methods of contraception, the reason for not using them was because of reasons related to (a) Method, 47, ((b) spouse in 87, (c) lack of access in 25, (d) fertility related in 81 and (e) health concerns in 77. After counselling, 263 females were ready to use contraception. Conclusions: If a female is counselled about the benefits, risk and side effects of the usage of reversible contraceptives. There can be a further improvement in the usage of contraceptives.